REFORMAS AL RÉGIMEN DE TERCERÍAS COADYUVANTES EN EL CÓDIGO DE PROCEDIMIENTO CIVIL, POR EL USO DOLOSO QUE SE LES DA A ESTAS, EN LA ACTUALIDAD - Guerra Patiño, Jhon Power (2016)
This research comprises a legal study of the problematic matrix in the thesis project, which refers in the main to misuse which nowadays has been given to this important institution called adjuvant Thirdness, which third outside the main contest, engage in the process by (supposedly) have inherent to the result of this interest. This legal problem is born as a result of the loan agreements contracted between the creditor and the debtor, because different commercial activities occurring today in our country, which are founded in credits that have the quality of executives, and that lack of fulfilment of civil obligations by the debtor taken to the knowledge of the competent judicial bodies, to be responsible for enforcing the provisions between the Contracting Parties. There is a judgment rendered by the Ministry of law, obliges the debtor to return credits to its creditor, the refusal of the first, the execution of the sentence, is produced by what the legislator to stipulated within the civil procedural law, the steps, seeking to restore such credits. Is there where there are third parties, who say they have interest in the execution of the process, and deduct third-party contributing to the last day of the auction, so that with this product, send them to also cancel its obligations. In the absence of a rule regulating the practice, some of these third-party proceedings is has been giving them misuse this on the grounds that the third-party claimant under an agreement with the debtor are unfair and 6 fraudulent way the contributing third party proceedings in execution of the Executive judgments, with the objective of damaging the heritage of the actor. It is so with the aim to provide direction and coherence to this research, according to the regulations of the academic Regimen and the new structure of the thesis, I made the study of the conceptual framework in which has been bibliographic knowledge collection and summary of empirical of each one of the themes of research knowledge using the scientific method with the analysis of the different concepts and themes for our work, and the synthesis and comments on other cases. In regards to the doctrinal framework our mental exercise was given in the search for the truth of our theme and hypothesis, with the aid of researchers who have tried the different fields of law and that have reinforced our ideas. The legal framework discussed the analysis of the Constitution in its share of rights and guarantees, as well as the incidence of the Organization of the State and its institutions in the development of our research; discussed and I try the characteristic of constitutional supremacy to identify any secondary rule may oppose the constitutional framework. Special care also the research resulted in the regulations that relate to our theme, in which we intend to introduce the respective legal reform.To comply with the opinion poll we use the survey, composed of five questions in which we explore the knowledge of the respondents, and as a result, we have the pictures and statistical graphs, as well as the interpretation of each question. Also noted the legal discussion, in which reform is sustained to propose whose work is given in the Constitution and analysis of the respective laws. It has been also guided the Foundation of this proposal. Finally it is worth mentioning that in accordance to the scientific method, in the analysis and treatment of the various frames, conceptual, doctrinal and legal, which are divided into topics, subtopics, and items, have been complied with to all the objectives proposed in the research project. Similarly concluded research has developed the conclusions and recommendations, which are an essential part of this research work, and which has allowed us to contrast the hypothesis raised promptly, which proved successful and veracity.